Delirium em idosos criticamente enfermos: um estudo utilizando a ferramenta CAM-ICU - Barros, Marcia Abath Aires de (2014)
Introduction: Delirium is a cognitive syndrome that frequently affects the severely ill elderly. It is characterized by an acute onset, fluctuations in awareness, attention and organization of thought, and is associated to unfavorable outcomes such as increased morbidity and mortality, prolonged hospital stay and permanent cognitive disability, especially when the elderly are subject of intensive care. The syndrome has many causes and requires preventive measures as the main therapeutic approach. However, we are not aware of the incidence of delirium and its determinants in the intensive care unit used in this research. Objectives: study the incidence of delirium in elderly admitted to the Intensive Care Unit (ICU) of Hospital Universitário Lauro Wanderley (HULW); characterize and associate demographic, epidemiological and clinical variables with the incidence of delirium. Methods: This is a cohort, prospective study with a quantitative approach. We used a sample of 55 elderly admitted in the ICU of HULW from september 2012 to march 2013. Data collection was carried out using a structured tool encompassing the studied variables, and the CAM-ICU method was used to identify delirium. The project was approved by the Ethical and Research Committee of HULW, with CAAE 05935312.2.00005183. Results: 47.27% of elderly were found to be affected with delirium. Women (57.69%) in the age group of 70-80 years-old (73.34%) and illiterate (45.46%) were affected more frequently. Elderly with delirium had more prolonged stay (42.31%) and greater mortality (57.69%) than the control group. Regarding invasive procedures, 46.15% of the elderly had been intubated, 96.15% had central venous accesses, and 88.46% had indwelling urinary catheters. Of note, 42.31% of elderly reported pain and 73.08% received restraining methods. Conclusions: Results show the need to screen delirium in a frequent basis in the ICU, in order to establish a multi-professional care plan to reduce its incidence, aiming for humanized care.